2019
DOI: 10.3389/fmars.2019.00347
|View full text |Cite
|
Sign up to set email alerts
|

Caribbean Sea Soundscapes: Monitoring Humpback Whales, Biological Sounds, Geological Events, and Anthropogenic Impacts of Vessel Noise

Abstract: Heenehan et al. Caribbean Marine Soundscapes health and species richness in Caribbean marine parks and demonstrate a surprising high anthropogenic foot print. Vessel traffic in particular contributes adversely to marine soundscapes, masking marine mammal sounds, potentially changing typical animal behavior and raising the risk of ship strike.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 63 publications
2
19
0
Order By: Relevance
“…In addition to the expected detections in the Caribbean (Heenehan et al, 2019;Whitehead & Moore, 1982), humpback whales were present from Cape Hatteras (region 9) to eastern Greenland (region 2) throughout the winter. Detections also remained high across these regions through spring and summer.…”
Section: Humpback Whalesmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition to the expected detections in the Caribbean (Heenehan et al, 2019;Whitehead & Moore, 1982), humpback whales were present from Cape Hatteras (region 9) to eastern Greenland (region 2) throughout the winter. Detections also remained high across these regions through spring and summer.…”
Section: Humpback Whalesmentioning
confidence: 69%
“…During the spring, summer, and fall, humpback whales in the western North Atlantic are found feeding in the Gulf of Maine, Gulf of St. Lawrence, and in waters off Nova Scotia, Newfoundland, and western Greenland (Katona & Beard, 1990). In winter months, a portion of the North Atlantic humpback whale population visits breeding grounds in the Caribbean and the Cape Verde Islands, and some individuals have even been identified in both breeding grounds (Heenehan et al., 2019; Stevick et al., 2016; Stevick, ØIen, & Mattila, 1998; Wenzel et al., 2009). Passive acoustic data from the western North Atlantic have revealed that humpback whales are present year‐round in the Gulf of Maine (Murray, Rice, & Clark, 2014; Vu et al., 2012), and in winter months off the Scotian Shelf (Kowarski, Evers, Moors‐Murphy, Martin, & Denes, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, ambient sound levels in Virgin Islands were lower and less variable compared to Stellwagen (Figure 4). An illustrative example of this difference is that humpback whale vocalizations are visible in the band sound level plots of Virgin Islands, but not in Stellwagen (Figure 3), although humpback whale vocalizations were detected and known to occur in both areas (Stanistreet et al, 2013;Heenehan et al, 2019). This inconsistency suggests that ambient sound levels, combined with other influencing factors (e.g., distance between conspecifics, number of individuals), are likely a contributing factor in the success or failure in detecting humpback whale vocalizations and other biological sources in a given region and season.…”
Section: Sound Levels Reveal Dominant Sourcesmentioning
confidence: 99%
“…NPOs and whale-watching companies). These data are highly valuable, often made by experienced observers able to accurately distinguish between species and some of them were used for scientific targeted studies ( Heenehan et al 2019 , Kennedy et al 2014 , Stevick et al 2016 , Stevick et al 2018 ). By their very heterogeneous nature, citizen science data are challenging to analyse ( Van Strien et al 2013 ).…”
Section: Introductionmentioning
confidence: 99%